2015
DOI: 10.1016/j.bbamem.2014.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Multiple nanosecond electric pulses increase the number but not the size of long-lived nanopores in the cell membrane

Abstract: Exposure to intense, nanosecond-duration electric pulses (nsEP) opens small but long-lived pores in the plasma membrane. We quantified the cell uptake of two membrane integrity marker dyes, YO-PRO-1 (YP) and propidium (Pr), in order to test whether the pore size is affected by the number of nsEP. The fluorescence of the dyes was calibrated against their concentrations by confocal imaging of stained homogenates of the cells. The calibrations revealed a two-phase dependence of Pr emission on the concentration (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 54 publications
9
97
2
Order By: Relevance
“…Previous studies on sub-microsecond pulses showed that increasing the number of monopolar pulses increased the number, but not the size of nanopores formed in the membrane41. A similar phenomena may be occurring here in which continued delivery of pulses 1 μs or shorter leads to the formation of numerous smaller pores rather than rapid cell membrane destruction caused by pore expansion and any lethal effects are due to mechanisms which occur post-treatment.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous studies on sub-microsecond pulses showed that increasing the number of monopolar pulses increased the number, but not the size of nanopores formed in the membrane41. A similar phenomena may be occurring here in which continued delivery of pulses 1 μs or shorter leads to the formation of numerous smaller pores rather than rapid cell membrane destruction caused by pore expansion and any lethal effects are due to mechanisms which occur post-treatment.…”
Section: Discussionsupporting
confidence: 72%
“…However, we hypothesize that the rapid charging and discharging of the cell membrane by the symmetric pulses inhibits pore expansion and instead results in an increase in the number, but not size of the pores formed41. However, it is unclear if these symmetric waveforms will be capable of transporting molecules across biological membranes efficiently.…”
Section: Discussionmentioning
confidence: 95%
“…At the same time, previous studies as well as in silico models found that shorter electric pulses produce fewer large-diameter pores [12, 14, 30, 36] and should be less damaging. Measuring the electroporative entry of a small cation such as Ca 2+ does not necessarily reveal the difference in pore size, hence it was probed with a larger Pr cation [15, 54]. …”
Section: Resultsmentioning
confidence: 99%
“…The technique of electric field delivery to individual cells was the same as reported previously [4, 1315, 20, 55]. Trapezoidal pulses of up to 20 kV amplitude and approximately 10 ns duration (at 50% height) were produced by a model FPG 20–1NM pulse generator (FID GmbH, Burbach, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation